Analisis Kebijakan Makro di Indonesia - Sumarmi, Saptaningsih (Akmenika, 2013)
This research make an analysis about influence of macro variables look towards inflation in Indonesia. The techni-ques at this research is used multiple linier regression with variable independent cen-tral government personnel expenditure, money supply look towards dependent varia-ble inflation. This result is showing that central government personnel expenditure have negative influence, and money supply have positive influence, so support previ-ous research.